Effects of Shea Butter. (Vitellaria paradoxa) Bark Extracts as Root Dips on Root-knot Nematodes (Meloidogyne Spp) Infestation and Growth of Tomato (Lycepersicon Iycopersicum L.) in Adamawa, Nigeria - Jada, M. Y.; Zirafilla, O. A.; M., Maryam Y.; J, Akwayamai P.; O, Pheobe A.; Timon, Freedom (African Journal of Biochemistry and Molecular Biology Research, 2025)
The management of root-knot nematodes(Meloidogyne spp.) presents significant challenges, particularly when synthetic (artificial) chemicals are employed. These chemicals are expensive for Nigerian farmers who lack resources and pose health and environmental risks. As a result, an experiment was conducted to evaluate the effectiveness of plant extracts, which are readily soluble and may be less expensive, as a root dip. A field study was carried out using root dips for tomato seedlings to evaluate the effectiveness of shea butter bark extracts against Meloidogyne spp. infestation. The field experiments were set up in a split plot design at the Loko and Mayo Belwa locations. There were sixteen treatments that were replicated three times, with four different concentrations (control, 10, 30, and 60%) and four different exposure times (5, 15, 30, and 60 minutes). The main plot was given concentrations, and the subplots were given exposure times. Data on the number of branches, fresh and dry shoot weight (g), and plant height (cm) following transplanting (WAT) were collected from the two sites. Galling index and fresh and dry root weight (g). ANOVA was used to analyze the data, and at the five percent probability level, means were separated using the Least Significant Difference (LSD). The field experiment's establishment and growth results at the Loko and Mayo Belwa locations demonstrated that the root dip exposed to 60% concentration in shea butter bark extracts for 60 minutes produced significant results (P=0). At 4, the plant height is higher (05). At Loko, WAT is 45.92, 69.75, and 73.25 cm, while at Mayo Belwa, it is 40.00, 57.00, and 67.25 cm. Additionally, it demonstrated a highly significant (P=0.01) difference between concentration and duration at 4.8, a significant (P=0.05) interaction between location and concentration at all times (4,8, and 10 WAT), and a significant (P=0.05) interaction between location and duration at 4WAT. 10WAT in addition to a significant (P=0.05) location difference. duration and focus at 4WAT exclusively. One could draw the conclusion that V. Extracts from paradoxa promoted establishment and growth by preventing or discouraging Meloidogyne spp. from attacking the dipped roots.